The framing of Islam by the international news agencies in the world section of The Star and The New Straits Times / Siti Hajar Abd Aziz, Shahril Anuar Abdul Ghalim and Noor Mayudia Mohd Mothar - Abd Aziz, Siti Hajar; Abdul Ghalim, Shahril Anuar; Mohd Mothar, Noor Mayudia (2010)
Perceptions about the world issues are very much shaped by the mass media. Newspapers audiences, particularly, are being forced to rely on the mass media towards the world they live in. When it comes to world news, the international news agencies are flooding the media around the world with an information flow structured based from the views of the developed world, thus, leading to news reports which are structured by the Westerner’s point of view. In view of this, the researcher studied two mainstream English newspapers in Malaysia, The Star and The New Straits Times for a month revealed that most stories on Islam revolves around war, crime and politics. The Star used most of the stories from the International News Agencies with little modification, the image of Islam projected negatively by The Star. The main frames are “Islam is inherently violent” and “does not go well with the concept of peace”. Although news reports in NST suggested that terrorism and wars are common in the Islamic countries, yet the tones also suggest that Islam is not the source of the act of extremism. The main frames in NST are “terrorism and wars are common in the Islamic countries, yet Islam is not to be blamed” and “the Muslim countries are slowly moving from extremism to peace and moderation.